Representasi Dan Citra Visual Artis Hijrah Di Media Online - Hesti Rahayu (DeKaVe, 2022)
The use of hijab in Indonesia is now very widespread. The rise of changes in the appearance of women in Indonesia for the hijab in public spaces, also colored by the hijab of artists who used to decorate the screen and social media, changed from previous appearances that tend to be sexy and open. The term migratory artist also surfaced. Research that discusses the visual image and representation of hijab women has indeed been done a lot, but specifically about hijrah artists who are veiled that appear in online media, is not much. For this reason, this study tries to describe how the representation and visual image of migrants in online media in Indonesia.This study rests on Stuart Hall's representation theory, visual image theory, and framing analysis. Samples taken by purposive sampling decided to observe Instagram belonging to migrants: Mulan Jameela, Laudya Cyntha Bella, Cut Meyriska, and Rachel Vennya. Each sample is discussed in terms of lifestyle, endorse, gossip about the artist's personal, as well as online media that often broadcast news about him.In the context of migratory artists, changing their appearance becomes an easy target for the audience. The artists emigrated as celebrities in online media, of course they could not be separated from how the visual image of their social media each dealing with online media portal framing. No matter how hard the artist tries to display a good self-image, there will always be netizens who comment in a scathing tone, balanced with positive comments from supporters. The representation and visual image of a migratory artist must be viewed positively, although it cannot be interpreted as a spectacular awakening of religiousity, but it is still limited to financial gain.